Biochemical and Mineral Changes in Green Gram Seeds: Raw vs. Sprout - Garaniya, N. H.; Bambhaneeya, S. M.; Patel, S. G.; Bambharolia, R. P.; Akabari, P. D. (International Journal of Economic Plants, 2025)
The present experiment was carried out during July–December, 2023 at the Department of Soil Science and Agricultural Chemistry, College of Agriculture, Navsari Agricultural University, Bharuch Campus, Gujarat, India, sought to investigate the biochemical composition, anti-nutritional elements, and mineral content of raw and sprouted green gram (Vigna radiata L.) across seven genotypes: GM-7, GBM-1, CO-4, GM-4, GM-6, MEHA, and GAM-5. Green gram seeds are nutrient-dense and extensively consumed; sprouting is known to boost their nutritional content. Moisture, total sugar, total protein, total phenol, methionine, and ascorbic acid were measured in both raw and sprouted seeds. It also looked at anti-nutritional compounds including phytic acid and minerals like calcium, magnesium, copper, iron, zinc, and manganese.The results showed that sprouting enhanced digestibility by increasing protein and decreasing sugar content. Phytic acid levels dropped considerably during sprouting, increasing nutrient availability. Mineral analysis demonstrated higher concentrations of key elements such as zinc, manganese, and iron during sprouting, whereas copper content decreased. These studies show the health benefits of consuming sprouted green gram, which has higher nutritional content and bioavailability.GM-4 exhibited the maximum moisture content in raw seeds, the highest carotenoids and calcium content in both raw and sprouted seeds, and significant protein levels. CO-4 excelled in sprouted form, with increased levels of total protein, total phenol, moisture, calcium, magnesium, and manganese. This study gives important insights into the nutritional content of green gram genotypes, which will aid in the selection of healthy variants for consumption and agriculture.